(untitled) (American Journal of Islam and Society, 2013)
Organized by the Standards and Metrology Institute for Islamic Countries (SMIIC), a subsidiary organ of the Organization of Islamic Cooperation (OIC), this forum was held on November 6-9, 2012, at Turkey’s Cornelia De Luxe Resort in Belek. The 160 delegates, who came from thirty-five countries, represented the National Standardisation Bodies (NSB), important national organizations of member countries, and such international organizations as the International Organisation for Standardisation (ISO), the International Electrotechnical Commission (IEC), the European Committee for Electrotechnical Standardisation (CENELEC), the Standardisation Organisation for the Cooperation Council for the Arab States of the Gulf (GSO), the Turkish Standards Institution (TSE), the Turkish Accreditation Agency (TURKAK), the Saudi Standards Metrology and Quality Organization (SASO), the Malaysian National Metrology Laboratory (SIRIM), the International Laboratory Accreditation Cooperation (ILAC), the OIC General Secretariat, the Commercial Cooperation of the Organization of Islamic Cooperation (COMCEC), the Statistical Economic and Social Research and Training Centre (SESRIC), and the Islamic Centre for the Development of Trade (ICDT). Also present were media outlets, representatives of various government bodies, officers from the Presidency of Religious Affairs of the Republic of Turkey (DIYANET), and academics from significant international universities. One of the forum’s main objectives was to create a platform to bring together experts and professionals from the fields of standardization, accreditation, and metrology in order to discuss these areas’ current circumstances within OIC member countries and at the international level ...